Expulsion of micronuclei containing amplified genes contributes to a decrease in double minute chromosomes from malignant tumor cells. Issue 6 (30th September 2013) - Ji, Wei; Bian, Zehua; Yu, Yang; Yuan, Chao; Liu, Yang; Yu, Lisa; Li, Chunxiang; Zhu, Jing; Jia, Xueyuan; Guan, Rongwei; Zhang, Chunyu; Meng, Xiangning; et al.
<x xml:space="preserve">Abstract</x> Double minute chromosomes (DMs) are a hallmark of gene amplification. The relationship between the formation of DMs and the amplification of DM‐carried genes remains to be clarified. The human colorectal cancer cell line NCI‐H716 and human malignant primitive neuroectodermal tumor cell line SK‐PN‐DW are known to contain many DMs. To examine the amplification of DM‐carried genes in tumor cells, we performed Affymetrix SNP Array 6.0 analyses and verified the regions of amplification in NCI‐H716 and SK‐PN‐DW tumor cells. We identified the amplification regions and the DM‐carried genes that were amplified and overexpressed in tumor cells. Using RNA interference, we downregulated seven DM‐carried genes, (NDUFB9, MTSS1, NSMCE2, TRIB1, FAM84B, MYC and FGFR2) individually and then investigated the formation of DMs, the amplification of the DM‐carried genes, DNA damage and the physiological function of these genes. We found that suppressing the expression of DM‐carried genes led to a decrease in the number of DMs and reduced the amplification of the DM‐carried genes through the micronuclei expulsion of DMs from the tumor cells. We further detected an increase in the number of γH2AX foci in the knockdown cells, which provides a strong link between DNA damage and the loss of DMs. In addition, the loss of DMs and the reduced amplification and expression of the DM‐carried genes resulted in a decrease in cell proliferation and invasion ability.